Lipid nutritional quality of industrialized enteral formulas available in the Brazilian market - Bolognese, Marciele Alves; Figueiredo, Alisson de Lima; Júnior, Oscar de Oliveira Santos; Visentainer, Jesuí Vergílio (Seven Editora, 2023)
The lipid nutritional quality of enteral formulas is an important factor to consider since the composition can affect the patient's lipid profile and immune response. Proper selection of the types and amounts of fatty acids present in enteral nutrition formulas play a key role in promoting health and preventing disease. Excessive consumption of saturated fatty acids and trans fatty acids may be associated with an increased risk of cardiovascular disease and an exacerbated inflammatory response. Therefore, it is essential that health professionals responsible for planning and prescribing enteral formulas consider not only the caloric needs, but also the quality of the lipids offered in the formulas. DOI:https://doi.org/10.56238/alookdevelopv1-077